Tinjauan Yuridis Penguatan Partisipasi Masyarakat Dalam Pembentukan Peraturan Desa Berdasarkan Pasal 24 Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Lubis, Ruaida; HB, Gusliana; Diana, Ledy (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to analyze the regulation related to community participation in the formation of village regulations as well as the ideal form of community participation in the formation of village regulations based on Article 24 of Law Number 6 Year 2014 on Villages. The type of research used by the author is normative legal research with qualitative data analysis that produces descriptive data. The results of this study state that the regulation of community participation in the formation of village regulations based on Article 24 of Law Number 6 of 2014 concerning Villages has failed because the level of community participation is still minimal. The author in this discussion provides an explanation of legal derivatives related to community participation in the formation of village regulations and the ideal form of participatory and transparent village regulations.